PERAN LKP LP3SI DALAM MENGEMBANGKAN KETERAMPILAN HIDUP DAN KESIAPAN KERJA MELALUI PROGRAM KURSUS BAHASA INGGRIS DAN KOMPUTER - Rosana Amalia Putri; Andi Sitti Saripah Ainun; Gusti Andre; Fadilla Ulfah; Ahmad Rifki (CV. Denasya Smart Publisher, 2026)
This study aims to examine the role of LKP LP3SI in developing participants’ self skills and work readiness through English language and computer course programs. The research was conducted using data collection techniques including observation, interviews, and documentation. The results indicate that LKP LP3SI plays an important role in equipping participants with skills required in the workplace, enhancing self confidence, and fostering independent and work ready attitudes. The learning process is supported by tutors who apply hands on practice methods, as well as by the support of owners and managers who carry a social mission in empowering participants. Although there are challenges such as limited facilities and varying levels of participant motivation, overall LKP LP3SI makes a tangible contribution to preparing skilled human resources who are ready to compete in the world of work.